The first species of Nandius Coulon in China (Coleoptera: Staphylinidae: Pselaphinae) - Jałoszyński, Paweł (Zootaxa, 2024)
Nandius Coulon was known as a Himalayan and sub-Himalayan genus, and is currently comprising four species distributed in Nepal and northern India. The first species from Yunnan, a subtropical region of China, is recorded, with description of Nandius yunnanicus sp. nov. Issues related to identification of Nandius, Pyxidicerus Motschulsky, and Parapyxidicerus Sawada are discussed, and an updated key to identification of Pyxidicerina genera is given.